Applied Biocatalysis in Europe: A Sustainable Tool for Improving Life Quality - Alcantara, Andres R; Plou, Francisco (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Applied biocatalysis and biotransformation, that is, the use of enzymes and whole-cell systems in manufacturing processes for synthetic purposes, has been experiencing a clear boom in recent years, which has led to the start of the so-called "fourth wave". In fact, the latest advances in bioinformatics, system biology, process intensification, and, in particular, enzyme-directed evolution (encouraged by the 2018 Nobel Prize awarded to F. Arnold), are widening the range of the efficacy of biocatalysts and accelerating the rate at which new enzymes are becoming available, even for activities not previously known. European scientists have been very actively involved in different aspects of this field. Nine contributions dealing with different aspects of applied biocatalysis developed by European researchers are gathered in this Special Issue